A model for upper extremity forces during the underwater phase of the front crawl - Jensen, R. K.; Blanksby, B. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
The research of Ringer and Adrian (1969) showed that elbow flexion and extension occur during the underwater phase of front crawl swimming. The thrust from the upper extremity action was estimated by Seireg and Baz (1971}, but their model did not allow for the relative motion of the segments of the upper extremity. Gallenstein and Huston (1973) used Hanavan's human body model (1964) to analyze a number of swimming actions, but did not investigate the upper extremity movements for the front crawl stroke. The purpose of the present study was to develop equations of motion for a model of the upper extremity during the underwater phase of front crawl swimming and to use these equations to demonstrate the effect of elbow flexion and extension on the forces acting on the upper extremity segments.